Estimating the transmissibility of hand, foot, and mouth disease by a dynamic model. (September 2019) - Chen, Shuilian; Yang, Dong; Liu, Ruchun; Zhao, Jin; Yang, Kewei; Chen, Tianmu
Abstract: Objective: Hand, foot, and mouth disease (HFMD) is a serious public health issue in many countries; however, its transmissibility in county-level outbreaks remains unclear. The aim of this study is to estimate the transmissibility of HFMD epidemics on both city level and county level, for a better understanding of the transmission dynamics of HFMD epidemics. Study design: Simulation based on data obtained from the China Information System for Disease Control and Prevention. Methods: The weekly number of reported HFMD cases from April 2009 to December 2017 in nine regions of Changsha City was collected. A susceptible-infectious-recovered model was used to estimate the transmissibility of HFMD. The reproduction number of reported cases during the ascending (denoted as R asc ) and descending (denoted as R des ) period was used to describe the transmissibility of HFMD. Results: The R asc and R des for HFMD in Changsha was 1.44 (95% confidence interval [ CI ]: 1.41–1.48) and 0.71 (95% CI : 0.69–0.73), respectively. There was no statistical significance of R asc values among nine regions ( F = 1.056, P = 0.396), nor of R des values among nine regions ( F = 1.676, P = 0.106). The average R asc (1.53, 95% CI : 1.46–1.61) from 2009 to 2012 was higher than the one (1.37, 95% CI : 1.34–1.40) from 2013 to 2017 ( t = 3.974, P < 0.001), but the average R des (0.67, 95% CI : 0.63–0.70) from 2009 to 2012 was lower than the one (0.74, 95% CI : 0.73–0.76) from 2013 to 2017 ( t = −3.751, P < 0.001). Conclusions: The epidemic of HFMD in Changsha City is still grim, and integrated strategies should be taken for controlling and preventing HFMD. Highlights: The reproduction number during the ascending period of hand, foot, and mouth disease was 1.44. The transmissibility of the disease was similar among nine regions of Changsha City. The transmissibility of the disease from 2013 to 2017 was different from the one from 2009 to 2012.